Combine like terms. 7 + 4x - 10x + 15
7 + 4x - 10x + 15 = -6x + 22, or 22 - 6x.
debnjerry|Points 68902|
Question
Updated 5/5/2015 2:46:23 PM
Edited by Andrew. [5/5/2015 2:46:22 PM], Confirmed by Andrew. [5/5/2015 2:46:23 PM]
s
Rating

Questions asked by the same visitor
Solve. 8 – 3x – x = 12
Weegy: 3x/6 + 1 = 7 x = 12 (More)
Question
Updated 5/5/2015 2:45:31 PM
8 – 3x – x = 12;
8 - 4x = 12;
-4x = 12 - 8;
-4x = 4;
x = 4/-4;
x = -1
32,001,517
*
Get answers from Weegy and a team of really smart live experts.
S
L
Points 866 [Total 3863] Ratings 2 Comments 846 Invitations 0 Offline
S
L
P
L
P
Points 819 [Total 6842] Ratings 1 Comments 809 Invitations 0 Online
S
L
P
R
P
R
L
P
P
C
R
P
R
L
P
R
Points 754 [Total 12845] Ratings 1 Comments 494 Invitations 25 Offline
S
L
P
1
Points 592 [Total 3448] Ratings 3 Comments 562 Invitations 0 Offline
S
L
Points 406 [Total 1899] Ratings 1 Comments 396 Invitations 0 Offline
S
L
Points 318 [Total 4702] Ratings 1 Comments 308 Invitations 0 Offline
S
L
1
Points 170 [Total 3481] Ratings 2 Comments 150 Invitations 0 Offline
S
L
Points 125 [Total 276] Ratings 3 Comments 95 Invitations 0 Offline
S
L
Points 85 [Total 244] Ratings 0 Comments 85 Invitations 0 Offline
S
L
L
Points 64 [Total 5352] Ratings 1 Comments 54 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.